Przyczynek do Sprężysto-Plastycznego Skręcania Prętów dla Skończonych Odkształceń - Mioduchowski, A. (Engineering Transactions, 1973)
In the paper is considered the problem torsion of a rod on the basisc of the of elastic-plastic geometry which takes into account the changes of the length and diameter of the rod. Using the approximate constitutive equations, the distribution of stresses in the cross-sectional arca of the materials and for loading and rod is shown, in the cases of compressible and incompressibleunloading processes.